Co Treatment With Biologic Agents and Immunotherapy in the Setting of irAEs of Difficult Management - Robles-Alonso, Virginia; Martínez-Valle, Fernando; Borruel, Natalia (Frontiers in Medicine, 2022)
In recent years, immunotherapy has become an important pillar of cancer treatment, with high response rates regardless of tumour histology or baseline mutations, sometime in patients without any alternative of treatment. Moreover, these treatments are moving from later line therapies to front-line therapies in the metastasic setting. However, immune activation associated with immune check-point inhibitors (ICI) is not selective and a large variety of immune-related adverse events, with an increasing frequency, have been associated with anti-PD1, anti-PD-1/L-1 and anti-CTLA-4 agents. In clinical trials, and sometimes also in real life practice, patients who develop severe toxicities on ICI-based therapies are usually not allowed to resume ICI once their disease progresses, because of the chance of developing severe irAEs on rechallenge with immunotherapies. Moreover, patients with irAEs suffer important side effects due to the high dose corticosteroids that are used to treat them. Therapy with ICI is sometimes the only alternative for certain patients, and for this reason co treatment with classic (DMARDS) or biologic immunosuppression therapy and ICI must be considered. Co-treatment with this type of immunosuppressant drugs, apart from allowing the maintenance of ICI therapy, drive to a lesser use of corticosteroids, with an improvement of the safety and quality of life of the patients. Such a tailored scheme of treatment is mostly an expert opinion based on recommendation and currently there is scarce evidence supporting it. Herein we present comprehensive, current recommendations and real-world data on the use of co-treatment with ICI and DMARDS and biologic immunosuppression.